Total Phenolics, Flavonoids, and Antioxidant Activities of Indonesian Apis Dorsata Honey Due to Heating - Akhmad Endang Zainal Hasan; Dimas Andrianto; Mega Safithri; Ilham Gilang Cahya Ahmada (Universitas Djuanda, 2023)
Honey is rich in phenolic and flavonoid compounds that have the potential as antioxidants. The heating treatment of honey is also known to affect the honey compound. This study aimed to determine the best Indonesian A. dorsata honey from various locations based on the level of total phenolics compounds, flavonoids, and antioxidant capacity due to variations in heating temperature. The procedures carried out in this study included: heating the sample with variations (room temperature, 65 oC, and 121 oC), measuring total phenolic content using the Folin-Ciocalteau method, measuring total flavonoid content using the AlCl3 colorimetric method, and testing antioxidant activity using the DPPH method. Each honey's total phenolic, flavonoid, and antioxidant activity are affected by its origin. The impact of heating at 65 oC and 121 oC resulted in various changes between honey samples (p<0.05). The best A. dorsata honey overall was found in Flores honey after heating at 121 oC heating treatment with total phenolic content of 4.96 mgGAE/mL, total flavonoids of 1.173 mg QE/mL, and IC50 5.76 g/L.